2018
DOI: 10.1177/0021998318805195
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and rheometric properties of natural rubber composites filled with untreated and chemically treated leather wastes

Abstract: In this work, the effect of the incorporation of leather wastes from chrome tanning on the mechanical and rheometric properties of natural rubber-based composite was evaluated. Chrome content in leather wastes diminished as a result of a chemical treatment with a sodium bicarbonate solution. The treatment also improved the tensile properties of composites with 0, 20 and 40 parts per hundred rubber of leather wastes with particle size between 590 and 840 µm. In a second stage of the experimental work, 0, 20, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…The peaks of the EDS spectrum corresponding to these atoms decrease or disappear when the neutralization treatment is carried out with the sodium bicarbonate solution. 12
Figure 4.SEM-EDS from leather wastes (a) untreated and (b) chemically treated with the sodium bicarbonate solution. SEM: scanning electron microscopy; EDS: energy dispersive X-ray spectroscopy.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peaks of the EDS spectrum corresponding to these atoms decrease or disappear when the neutralization treatment is carried out with the sodium bicarbonate solution. 12
Figure 4.SEM-EDS from leather wastes (a) untreated and (b) chemically treated with the sodium bicarbonate solution. SEM: scanning electron microscopy; EDS: energy dispersive X-ray spectroscopy.
…”
Section: Resultsmentioning
confidence: 99%
“…These composites have exhibited a high compatibility between the residues and the matrix, favoring the improvement in mechanical properties such as hardness and tensile strength. 612 Additionally, it has been found that the addition of these residues aids the incorporation of up to 600 phr of recycled rubber into rubber formulations, facilitating their processing without a significant decrease of the vulcanization parameters. 7,8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, rubber composites incorporated with various reinforcing materials are gaining momentum due to the wide array of industrial applications connected to day-to-day life and in fields like aircraft tires, sports goods, gaskets, belts, etc. 1517 These materials in NR are highly effective in enhancing the processing and mechanical properties of the prepared composites. Numerous reports on the reutilization of various industrial wastes as reinforcing fillers are available in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to the greater awareness of environmental issues, the management of solid tanned waste over the past few years has taken on a primary role for the tanning industries. Interest has recently renewed for solid tanned waste in the field of polymers [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%